Nanoscale layer of a minimized defect area of graphene and hexagonal boron nitride on copper for excellent anti-corrosion activity. (8th November 2021) - Hwang, Jae Hun; Shrestha, Bishnu Kumar; Kim, Jun Hee; Seo, Tae Hoon; Park, Chan Hee; Kim, Myung Jong
Abstract: In this work, we synthesized a monolayer of graphene and hexagonal boron nitride (hBN) using chemical vapor deposition. The physicochemical and electrochemical properties of the materials were evaluated to determine their morphology. High-purity materials and their atomic-scale coating on copper (Cu) foil were employed to prevent fast degradation rate. The hexagonal two-dimensional (2D) atomic structures of the as-prepared materials were assessed to derive their best anti-corrosion behavior. The material prepared under optimized conditions included edge-defect-free graphene nanosheets (∼0.0034 μ m 2 ) and hBN (∼0.0038 μ m 2 ) per unit area of 1 μ m 2 . The coating of each material on the Cu surface significantly reduced the corrosion rate, which was ∼2.44 × 10 –2 /year and 6.57 × 10 –3 /year for graphene/Cu and hBN/Cu, respectively. Importantly, the corrosion rate of Cu was approximately 3-fold lower after coating with hBN relative to that of graphene/Cu. This approach suggests that the surface coating of Cu using cost-effective, eco-friendly, and the most abundant materials in nature is of interest for developing marine anti-corrosion micro-electronic devices and achieving surface modification of pure metals in industrial applications.